Fertilization-Defective Gametophytic Mutant Screening: A Novel Approach - Adhikari, Prakash Babu; Liu, Xiaoyan; Kasahara, Ryushiro D. (Frontiers in Plant Science, 2020)
Gametophytic mutants share very small proportion of the total mutants generated by any mutagenic approach; even rarer are the fertilization-defective gametophytic mutants. They require an efficient and targeted strategy instead of ‘brute force’ screening approach. The classical gametophyte mutant screening method, mainly based on the segregation distortion, can distinguish gametophytic mutants from the others. However, the mutants pooled after the screening constitute both fertilization-defective and developmental-defective gametophytic mutants. Until recently, there has not been any straight forward way to screen the former from the latter. Additionally, most of the mutations affecting both gametes are lost during the screening process. The novel gametophyte screening approach tend to circumvent those shortcomings. This review discusses on the classical approach of gametophytic mutant screening and focuses on the novel approach on distinguishing fertilization-/developmental-defective gametophytic mutants (both male and female). It offers an empirical basis of screening such mutants by taking in the consideration of earlier studies on fertilization failure, initiation of seed coat formation, and fertilization recovery system in plants.